THE RELATIONSHIP BETWEEN IBN KHALDUN AND ADAM SMITH - Toboli , Abulkasem (Dirasat in Economics and Business, 1971)
Economics is a modern science. Before 1776 most of the economic ideas were mixed with either philosophy or politics. A good example is the work of Ibn Khaldun. His economic ideas were mixed with either ethics or politics. As an example, when he discussed the empirical labor theory of value, he mixed it with the ethics of labor. Charles Issawi remarked that << Ibn Khaldun's remarks on economic theeory deserve attention. »>1